Energia e proteína para frangos de corte fêmeas em ambiente termoneutro e em estresse por calor - Anna Rosa Chagas Abreu (2015)
Two experiments were conducted to evaluate the effects of energy levels, 3150 kcal/kg and 3200 kcal/kg, and crude protein, 19,2% and 21%, in diet for female broilers, in growth phase, under thermoneutral conditions (experiment I) or cyclic heat stress (experiment II). In each experiment, 288 broilers were used, distributed in a completely randomized factorial 2x2 (two energy levels x two levels of crude protein in the diet), using 12 broilers per experimental unit and 6 replicates per treatment. In the first experiment, thermoneutral condition, the treatment did not affect the performance variables (P>0.05). There was interaction between energy and crude protein of diet for all variables of metabolism experiment (CDMS, CDCP, CDEE, AME and AMEn) (P0.05). The treatments did not affect the relative weight of liver and intestines (P>0.05), but the highest level of crude protein resulted in higher breast weight (P0.05) and the use of 3200 kcal/kg of energy level resulted in a reduction in abdominal fat weight, but only when used with 21% of crude protein in diet. The treatments did not influence broilers physiological index in none of the ages (P>0.05). The higher energy level and higher protein level, independently, resulted in higher cost of feed per pound of chicken (P0.05). In the second experiment, the only performance variable influenced by the treatments was feed intake (P 0.05), in which the reduction of energy levels resulted in an increase in feed intake. In the metabolism assay, the interaction between energy levels and dietary crude protein was significant for CDMS, AME and AMEn (P 0.05). The highest crude protein level in diet reduced the CDCP (P0.05). The highest level of energy and crude protein in diet, independently, resulted in increased CDEE (P0.05). The lower level of protein led to an increase in relative liver weight (P0.05). The treatments did not influence the relative weight of intestines, breast, thigh and abdominal fat (P>0.05). There was interaction between energy and broilers age for rectal temperature (P0.05), in which the energy level of 3200 kcal/kg increased the rectal temperature of broilers, but only in the 26th day of age. The treatments did not affect respiratory rate of broilers (P>0.05). As well as in thermoneutral conditions, in the cyclic heat stress condition, the highest energy and protein level, independently, resulted in a higher cost of feed per pound of chicken (P0.05). The lower nutritional levels, 3150 kcal/kg of energy and 19,2% of crude protein in diet, should be used for female broilers in growth phase under thermoneutral or cyclic heat stress conditions, once the increased nutritional levels did not affect broilers performance and increased the production cost.